An examination of (proximal determinants of) online aggression perpetration among adults aged 19 to 79 - Pabian, Sara (Deviant behavior, 2025)
Online aggression is not only prevalent among adolescents, but also among adults of all ages. Most of the previous studies among adults have focused on limited age cohorts, for instance, university populations. The present study’s aim is to investigate how age is related to online aggression, as well as to potential risk factors of this behavior among adults. To this aim, a cross-sectional survey was administered among 2,000 Belgian adults aged 19-79. Results showed a negative linear association between age and online aggression perpetration. Age was also negatively linearly related to victimization and acceptance of online aggression, whereas quadratic (U-parabola) relationships were found between age and online moral disengagement strategies (OMD). Different potential risk factors of online aggression perpetration were found for different age groups. Significant associations between (some) OMD strategies and perpetration were only found in the age groups 46-55 and 56-65. Acceptance of online aggression was associated with perpetration among 18-25- and 66±year-olds. For all age groups, online victimization was associated with perpetration. This association was the strongest among 26-36- and the lowest among 66±year-olds. The results imply that for developing effective intervention and/or prevention campaigns aiming adults, a one-size-fits-all strategy should be avoided.